Arisaema nayamakkadense (Araceae, Section: Sinarisaema) a new species from south Western Ghats, India - Mathew, Jose; Salim, Pichan Mohammed (Phytotaxa, 2025)
A new species of Arisaema with male, monoecious, and female life forms, A. nayamakkadense from south Western Ghats is described. The taxonomic description, morphological differences to the allied taxa, A. leschenaultii, and colour photographs are provided to facilitate easy identification in the field.